2013
DOI: 10.1371/journal.pone.0067989
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Localization and Possible Function of Calcium-Activated Chloride Channel Anoctamin 1 in the Mammalian Retina

Abstract: Calcium (Ca2+)-activated chloride (Cl−) channels (CaCCs) play a role in the modulation of action potentials and synaptic responses in the somatodendritic regions of central neurons. In the vertebrate retina, large Ca2+-activated Cl− currents (ICl(Ca)) regulate synaptic transmission at photoreceptor terminals; however, the molecular identity of CaCCs that mediate ICl(Ca) remains unclear. The transmembrane protein, TMEM16A, also called anoctamin 1 (ANO1), has been recently validated as a CaCC and is widely expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…Thus, TMEM16A appears essential for exocytosis. A role of different TMEM16 paralogues for synaptic transmission has been proposed recently (33)(34)(35). We examined TMEM16A-expressing HEK293 cells and noticed this enhanced membrane capacitance.…”
Section: Tmem16a Controls Intracellular Ca 2+ Signals and Membrane Exmentioning
confidence: 78%
“…Thus, TMEM16A appears essential for exocytosis. A role of different TMEM16 paralogues for synaptic transmission has been proposed recently (33)(34)(35). We examined TMEM16A-expressing HEK293 cells and noticed this enhanced membrane capacitance.…”
Section: Tmem16a Controls Intracellular Ca 2+ Signals and Membrane Exmentioning
confidence: 78%
“…The channels do not show pronounced inactivation and are thought to serve as a link in a feedback regulatory chain that limits transmitter release (Thoreson et al, 2000, 2002, 2003; Mercer et al, 2011). ANO 1 channels have been reported to be expressed in rod and cone terminals (Mercer et al, 2011; Jeon et al, 2013). We have recently found that ANO 2 is specifically expressed in rod terminals and absent from cone photoreceptors, which suggests a distinct role in the regulation of transmitter release under scotopic conditions (Dauner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The tail current of the hERG was not significantly changed after 5 min of 0.1% DMSO (95.170.7% of the control, n ¼12). Western blot analyses were performed with minor modifications, as described previously (Jeon et al, 2013). Briefly, cells were homogenized in ice-cold RIPA buffer (50 mM Tris buffer, pH 8.0; 150 mM NaCl; 1% NP-40; 0.5% deoxycholate; and 0.1% SDS).…”
Section: Methodsmentioning
confidence: 99%